Control of Sorghum Shootfly by Carbofuran Seed Treatment - Kulkarni, K A; Jorwani, M G (Annals of Arid Zone, 2016)
Studies on the efficacy OF carbofuran seed dress for sorghum shootfly control was made at the Regional Research Station, Dharwar and medium research station, Bijapur in kharif and rabi seasons of 1973-74 and 1974-75 on CSH-1 and R-16. The results indicated that carbofuran treated seeds tried alone or in combination of untreated seeds in the ratio of 80 : 20 and 60 : 40 gave effective control of sorghum shootfly. Cost benefit studies indicated that among the significant treatments, 80 : 20 ratio was found to be ’economical,